PCR-RFLP Design for Authentication of Red Snapper Species Based on CYB Gene - Timbuleng, Kevin; Kolondam, Beivy J; Katili, Deidy (Sam Ratulangi University, 2021)
The PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) technique is a species identification method that can facilitate food inspection agencies to overcome mislabelling. In addition, this technique is simple, fast, powerful, and cheap compared to DNA barcodes. This study aimed to accommodate the problem in determining restriction endonuclease enzymes for the digestion of PCR end products through the design of snapper species authentication using the CYB gene in silico. Differentiation of CYB gene sequences with DNA barcoding showed that all species could be differentiated with the highest similarity level in Red Fish (Sebastes) species by 98.9% and snapper species between L. malabaricus and L. erythropterus by 99.8%. Enzyme tracing based on sequences variation of snapper species with substitution species found three potential enzymes from the CYB gene sequence, namely, Accl, Fnu4HI, and Tsp45I. Where all these enzymes can discriminate red snapper species among other.Key words: PCR-RFLP; CYB gene; Red snapperAbstrakTeknik PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) merupakan metode identifikasi spesies yang dapat memfasilitasi lembaga inspeksi makanan untuk mengatasi mislabelling. Selain itu, teknik ini sederhana, cepat, kuat, dan murah dibandingkan dengan barcode DNA. Penelitian ini bertujuan untuk mengakomodasi masalah dalam menentukan enzim restriksi endonuklease untuk digesti produk akhir PCR lewat perancangan autentikasi spesies ikan kakap menggunakan gen CYB secara in silico. Diferensiasi sekuens gen CYB dengan DNA barcoding menunjukkan semua spesies dapat dibedakan dengan tingkat kesamaan tertinggi pada spesies Red Fish (Sebastes) sebesar 98,9% dan spesies kakap antara L. malabaricus dan L. erythropterus sebesar 99,8%. Penelusuran enzim berdasarkan variasi sekuens spesies kakap dengan spesies substitusi ditemukan sebanyak tiga enzim yang berpotensi yaitu, Accl, Fnu4HI, dan Tsp45I. Semua enzim tersebut dapat memdiskriminasikan spesies kakap merah dari spesies lainnya.Kata kunci: PCR-RFLP; gen CYB; ikan kakap merah